IMPLEMENTASI ISLAMIC ENTREPRENEURSHIP MELALUI MANAJEMEN PENDIDIKAN DI SEKOLAH DASAR ISLAM TERPADU - Ainil Fhadilah; Adilla, Ulfa; Yulia Friska, Sonia; Dewi Sara; Sopiati (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This study aims to analyze the implementation of Islamic entrepreneurship through educational management at SD IT Al-Akhyar Muara Bungo. This research employs a qualitative approach with a descriptive design. Data collection techniques include observation, interviews, and documentation, involving school principals, teachers, and students as research subjects. Data analysis was conducted through data reduction, data display, and conclusion drawing, while data validity was ensured through source and method triangulation.The findings reveal that the implementation of Islamic entrepreneurship at SD IT Al-Akhyar Muara Bungo is carried out through integration into learning activities, market day programs, and the habituation of Islamic values such as honesty, trustworthiness, responsibility, and hard work. Educational management plays a crucial role in the success of the program through systematic planning, organizing, implementation, and evaluation. Teachers act as facilitators in guiding students, while the support of school principals and parents strengthens program implementation. However, several challenges were identified, including limited instructional time, insufficient facilities, and varying levels of teacher competence in integrating Islamic entrepreneurial values. Nevertheless, the program has generally contributed positively to students’ character development, self-confidence, social skills, and financial literacy. Therefore, strengthening educational management, improving teacher competence, and developing a more structured curriculum are necessary to optimize and sustain the implementation of Islamic entrepreneurship.